Comparing the literatures : literary studies in a global age - Damrosch, David (Princeton University Press, 2020)
"In this new history of comparative literature, David Damrosch argues that the discipline is not dead or unmoored, as some critics claim, but continues to face some of the same questions that have shaped it since its beginnings in the nineteenth century. Damrosch traces the discipline's past in order to clarify its present tensions and concerns, and to rethink the fundamental terms of literary analysis, methods, and training that will guide the discipline's future. Literary studies today are in a time of rapid change, fueled by the expansive and disruptive forces of globalization. More works than ever circulate worldwide in English and in translation, and even national traditions are increasingly seen in transnational terms. How can scholars and teachers encompass this expanding literary universe? What linguistic and cultural resources do they need, and how can they best address the politics of a very uneven global field? The discipline of comparative literature has long sought to develop effective theories and methods of broad-based study, but ideas based on national canons in a handful of Western European countries no longer seem adequate even for the study of national literatures themselves. Comparing the Literatures integrates comparative, postcolonial, and world-literary perspectives and seeks common ground. Looking both at institutional forces and at key episodes in the life and work of comparatists who have struggled to define and to redefine the fundamental terms of literary analysis, from language to literature to theory to comparison itself, Damrosch offers a comprehensive overview of the history and current prospects of comparative studies in a globalizing world"--